Lactic Acid Fermentation Is Required for NLRP3 Inflammasome Activation - Lin, Hsin-Chung; Chen, Yu-Jen; Wei, Yau-Huei; Lin, Hsin-An; Chen, Chien-Chou; Liu, Tze-Fan; Hsieh, Yi-Lin; Huang, Kuo-Yang; Lin, Kuan-Hung; Wang, Hsueh-Hsiao; Chen, Lih-Chyang (Frontiers in Immunology, 2021)
Activation of the Nod-like receptor 3 (NLRP3) inflammasome is important for activation of innate immune responses, but improper and excessive activation can cause inflammatory disease. We previously showed that glycolysis, a metabolic pathway that converts glucose into pyruvate, is essential for NLRP3 inflammasome activation in macrophages. Here, we investigated the role of metabolic pathways downstream glycolysis – lactic acid fermentation and pyruvate oxidation – in activation of the NLRP3 inflammasome. Using pharmacological or genetic approaches, we show that decreasing lactic acid fermentation by inhibiting lactate dehydrogenase reduced caspase-1 activation and IL-1β maturation in response to various NLRP3 inflammasome agonists such as nigericin, ATP, monosodium urate (MSU) crystals, or alum, indicating that lactic acid fermentation is required for NLRP3 inflammasome activation. Inhibition of lactate dehydrogenase with GSK2837808A reduced lactate production and activity of the NLRP3 inflammasome regulator, phosphorylated protein kinase R (PKR), but did not reduce the common trigger of NLRP3 inflammasome, potassium efflux, or reactive oxygen species (ROS) production. By contrast, decreasing the activity of pyruvate oxidation by depletion of either mitochondrial pyruvate carrier 2 (MPC2) or pyruvate dehydrogenase E1 subunit alpha 1 (PDHA1) enhanced NLRP3 inflammasome activation, suggesting that inhibition of mitochondrial pyruvate transport enhanced lactic acid fermentation. Moreover, treatment with GSK2837808A reduced MSU-mediated peritonitis in mice, a disease model used for studying the consequences of NLRP3 inflammasome activation. Our results suggest that lactic acid fermentation is important for NLRP3 inflammasome activation, while pyruvate oxidation is not. Thus, reprograming pyruvate metabolism in mitochondria and in the cytoplasm should be considered as a novel strategy for the treatment of NLRP3 inflammasome-associated diseases.